Measurement of immature platelets with Abbott CD-Sapphire and Sysmex XE-5000 in haematology and oncology patients - Meintker, Lisa; Haimerl, Maria; Ringwald, Juergen; Krause, Stefan (Clinical Chemistry and Laboratory Medicine, 2013)
Background: Measurement of immature platelets was introduced into routine diagnostics by Sysmex as immature platelet fraction (IPF) some years ago and recently by Abbott as reticulated platelet fraction (rPT). Here, we compare both methods. Methods: We evaluated the precision and agreement of these parameters between Sysmex XE-5000 and Abbott CD-Sapphire in three distinct thrombocytopaenic cohorts: 30 patients with beginning thrombocytopaenia and 64 patients with recovering platelets (PLT) after chemotherapy, 16 patients with immune thrombocytopaenia (ITP) or heparin-induced thrombocytopaenia type 2 (HIT) and 110 additional normal controls. Furthermore, we analysed, how IPF/rPT differed between these thrombocytopaenic cohorts and controls. Results: Both analysers demonstrated acceptable overall precision (repeatability) of IPF/rPT with lower precision at low PLT counts. IPF/rPT artificially increased during storage of blood samples overnight. Inter-instrument comparison showed a moderate correlation (Pearson rÂ0.38) and a systematic bias of 1.04 towards higher IPF-values with the XE-5000. IPF/rPT was highest in recovering thrombopoesis after chemotherapy and moderately increased in ITP/HIT. The normal range deduced from control samples was much narrower with CD-Sapphire (1.0%-3.8%, established here for the first time) in comparison to XE-5000 (0.8%-7.9%) leading to a smaller overlap of samples with increased PLT turnover and normal controls. Conclusions: IPF and rPT both give useful information on PLT turnover, although the two analysers only show a moderate inter-instrument correlation and have different reference ranges. A better separation of patient groups with high PLT turnover like ITP/HIT from normal controls is obtained by CD-Sapphire. © 2013 by Walter de Gruyter Berlin Boston.
Created from Fastlane, Scopus look-up
Keywords: heparin-induced thrombocytopaenia type 2 (HIT); immature platelet; immature platelet fraction (IPF); immune thrombocytopaenia (ITP); reticulated platelet; thrombocytopaenia